Application of loop mediated isothermal amplification (LAMP) assays for the detection of Onchocerca volvulus, Loa loa and Mansonella perstans in humans and vectors - Amambo, Glory Ngongeh; Innocentia, Ngong; Abong, Raphael Awah; Fombad, Fanny Fri; Njouendou, Abdel Jelil; Nietcho, Franck; Ekanya, Relindis; Kien, Chi Anizette; Ebai, Rene; Lenz, Benjamin; Ritter, Manuel; Esum, Mathias Eyong; et al. (Frontiers in Tropical Diseases, 2023)
Conventional diagnosis of filarial infections is based on morphological identification of microfilariae using light microscopy and requires considerable expertise, is time-consuming, and can be subjective. Loop-mediated isothermal amplification (LAMP) has advantages over microscopy or PCR because of its operational simplicity, rapidity and versatility of readout options. LAMP assays represent a major step forward in improved filarial diagnostic tools suitable for low resource settings and field applicability. The study goal was to retrospectively evaluate the performance and suitability of the O-150, RF4, and Mp419 LAMP assays for diagnosing Onchocerca volvulus, Loa loa and Mansonella perstans infections, respectively, in humans and vectors under experimental and natural field conditions. Surveys were conducted in four health districts of Cameroon using skin snip and thick blood film methods to detect skin (O. volvulus) and blood (L. loa and M. perstans) dwelling microfilaria in humans. Engorged vectors (Simulium spp., Chrysops spp., and Culicoides spp.) were evaluated by LAMP. Dissected, wild-caught vectors were also analyzed. LAMP showed a prevalence of 40.4% (O. volvulus), 17.8% (L. loa) and 36.6% (M. perstans) versus 20.6% (O. volvulus), 17.4% (L. loa) and 33.8% (M. perstans) with microscopy. Simulium spp. were dissected for microscopy and pooled for LAMP. The O-150 LAMP assay infection rate was 4.3% versus 4.1% by microscopy. Chrysops spp. were dissected and analyzed individually in the LAMP assay. The RF4 LAMP assay infection rate was 23.5% versus 3.3% with microscopy. The RF4 LAMP assay also detected parasites in Chrysops spp. fed on low microfilaremic volunteers. The Mp419 LAMP assay infection rate was 0.2% for C. milnei and 0.04% for C. grahamii, while three other species were LAMP-negative. The sensitivity, species specificity, rapidity and ease of its use of these filarial LAMP assays, and validation of their performance in the field support use as alternatives to microscopy as diagnostic and surveillance tools in global health programs aimed to eliminate onchocerciasis.